Service quality-satisfaction-intention relationships in the internet retail context - Siohong, Tih; Sean, Ennins (Penerbit Universiti Kebangsaan Malaysia, 2006)
This paper examines the theoretical relationships between service quality, customer satisfaction and purchase intention in the internet context across products. It demonstrates to practitioners the value of investing in service quality improvement and provides possible answers to the general speculation that offering "search" products over the internet may be more promising than offering "experience" products. Initially, a classification study was conducted to identify the classification of products from the users' perspective. Then, a web survey resulting in 636 responses was carried out to test the hypothesised model. The results showed that the mediated relationships between service quality, satisfaction and repurchase intentions were supported in the internet context and this relationship was retained across three services: internet banking, airline ticketing and book retailing. The findings suggest that an advantageous position in the internet retail market may be gained through improvement in the overall service quality performance rather than relying on the classification of product offered to determine increase in internet purchases. Suggestions for further research are also provided.